IMPROVING STUDENTS’ SPEAKING ABILITY THROUGH DEBATE TECHNIQUE - Desita, Lidya Ratna; Supardi, Iwan; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract: The purpose of conducting this research is to improve students’ speaking ability in giving opinion and responding to another’s opinion through debate. The methodology of this research is a classroom action research which consisted of 3 cycles. The subject of this research was the eighth grade students of SMPN 7 Sungai Raya, B class which consists of 26 students. To collect the data, the researcher used observation checklist and field notes. Through observation checklist the researcher observed students’ activity in the classroom and by using field notes the researcher reflected the problem found.  Based on the research findings, debate technique which was applied to the subjects of research showed the improvement of students’ speaking ability. Based on the result of the researcher’s observation using observation checklist and form of field notes, it can be seen that students’ speaking ability in giving opinion and responding to another’s opinion have been improved. The percentage of students’ activity in the classroom when debate, in the first cycle was 57%, in the second cycle was 67% and the third cycle was 76%. It indicated that debate technique had improved students’ speaking ability in giving opinion and responding to another’s opinion. Key words: Speaking Ability, Debate Technique, Classroom Action Research Abstrak: Tujuan dari pelaksanaan penelitian ini adalah untuk meningkatkan kemampuan berbicara siswa dalam mengungkapkan pendapat dan menganggapi pendapat yang lainnya melalui debat. Metode yang digunakan di penelitian ini adalah Penelitian Tindakan Kelas (PTK). Subjek penelitian adalah murid kelas 8 dari SMPN 7 Sungai Raya, kelas B yang terdiri dari 26 murid. Peneliti menggunakan observasi ceklis dan field note. Melalui obsevasi ceklist peneliti mengamati kegiatan murid di dalam kelas dan peneliti merefleksi masalah yang ditemukan menggunakan field note. Berdasarkan hasil penelitian, teknik debat yang diterapkan kepada subjek penelitian menunjukkan peningkatan kemampuan bicara murid dalam memberikan pendapat dan menanggapi pendapat yang lain. Berdasarkan observasi peneliti dapat terlihat bahwa kemampuan murid dalam mengungkapkan pendapat dan menanggapi pendapat telah meningkat. Persentase dari kegiatan siswa di dalam kelas ketika debat, untuk cycle pertama adalah 57%, untuk cycle kedua adalah 67% dan cycle ketiga dalah 76%. Hasil tersebut membuktikan bahwa debat dapat meningkatkan kemampuan berbicara siswa dalam mengungkapkan pendapat dan menanggapi pendapat.   Kata kunci: Kemampuan Berbicara, Teknik Debat, Penelitian Tindakan Kelas